TOURISM AND RECREATION POTENTIAL OF THE YAVORIVSKA UNITED TERRITORIAL COMMUNITY OF LVIV OBLAST, AS A PRIORITY FACTOR FOR ITS SUSTAINABLE DEVELOPMENT - PANKIV, Natalia; PISOTSKYІ Bohdan (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the tourism and recreation potential of Yavorivska OTG of Lviv Oblast and examines the prerequisites for the formation of the concept of sustainable development and the prospects for its implementation in the community. Special attention is paid to the analysis of natural, cultural, historical and infrastructural resources of the region, which allows to understand the uniqueness and diversity of tourist offers. A comprehensive review of the region’s tourism opportunities, the dynamics of development indicators, and the performance indicators of institutions and entities regulating the tourism industry were analyzed. The existing programs and strategies of sustainable development were assessed, and their role in increasing the district’s competitiveness was determined. The problematic aspects and prospects of the district’s transition to sustainable development were studied, and a SWOT analysis was carried out. Recommendations for the development of tourism and promotion of the tourist brand of Yavorivska hromada are presented. A sustainable development program and measures have been developed for the Yavoriv OTG, which take into account the need for a systematic approach to solving problems and achieving the goals of sustainable development of tourism in the region.